2022
DOI: 10.1186/s40246-022-00400-4
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive fetal genotyping of single nucleotide variants and linkage analysis for prenatal diagnosis of monogenic disorders

Abstract: Background High-cost, time-consuming and complex processes of several current approaches limit the use of noninvasive prenatal diagnosis (NIPD) for monogenic disorders in clinical application. Thus, a more cost-effective and easily implementable approach is required. Methods We established a low-cost and convenient test to noninvasively deduce fetal genotypes of the mutation and single nucleotide polymorphisms (SNPs) loci by means of targeted ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Furthermore, we adopted amplicon sequencing to construct the DNA library, which reduces the cost to less than half of that of the hybridization capture method. Wu et al demonstrated the feasibility of amplicon sequencing for NIPD by designing 20-30 amplicons flanking related pathogenic variants in seven different diseases (Wu et al, 2022). In consideration of the high recombination rate upstream of the DUX4 gene (Pini et al, 2023), we increased the number of SNPs to 402, which enabled more accurate detection of recombination events.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we adopted amplicon sequencing to construct the DNA library, which reduces the cost to less than half of that of the hybridization capture method. Wu et al demonstrated the feasibility of amplicon sequencing for NIPD by designing 20-30 amplicons flanking related pathogenic variants in seven different diseases (Wu et al, 2022). In consideration of the high recombination rate upstream of the DUX4 gene (Pini et al, 2023), we increased the number of SNPs to 402, which enabled more accurate detection of recombination events.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed 32 NPPK relevant studies since 2013, totaling 389 cases (Table S1). 1–5,17,19–43 Twenty‐nine pathogenic mutations in SERPINB7 were summarized. Only eight out of 389 NPPK cases with a single heterozygous mutation were identified as patients due to either clear family history or undetermined second mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, for population monitoring of trisomy 21 NIPD offers completely new aspects with respect to population-wide ascertainment in early pregnancy. Moreover, direct haplotyping has been successfully applied for NIPD of monogenic disorders [ 90 92 ] including triplet-repeat expansion diseases [ 93 ]. Based on the significant progress of NIPD in the past few years, it is realistic to assume that in the future haplotyping of aneuploidies is possible as well as differentiation between MI and MII errors.…”
Section: Concept For Population Monitoring Of Down Syndromementioning
confidence: 99%